Corrections to “A Novel Approach Based on Machine Learning, Blockchain and Decision Process for Securing Smart Grid” - Nabil Tazi Chibi; Omar Ait Oualhaj; Wassim Fassi Fihri; Hassan El Ghazi (IEEE Access)
Presents corrections to the paper, (Corrections to “A Novel Approach Based on Machine Learning, Blockchain and Decision Process for Securing Smart Grid”).